Vaccination with Bordetella pertussis-Pulsed Autologous or Heterologous Dendritic Cells Induces a Mucosal Antibody Response In Vivo and Protects against Infection - George-Chandy, Annie (American Society for Microbiology, 2001)
This study demonstrates for the first time that vaccination with either autologous or heterologous dendritic cells (DC) pulsed with specific antigen induces protective immune responses against noninvasive bacteria, namely Bordetella pertussis. The DC-mediated protection is associated with strong B. pertussis-specific immunoglobulin G (IgG) and IgA responses in the lung.